The power of a parable. The religious “origins” of business ethics - Sójka, Jacek (Człowiek i Społeczeństwo, 2016)
Business ethics deals with ethical aspects of management and entrepreneurship, activities closely linked to “this world’s” problems. Surprisingly enough religious traditions have their impact on the argumentation in this field. The paper focuses on two biblical parables: on the talents and on the good Samaritan. Both are not only present in business and management literature but also widely discussed in the context of today’s economy and society. The first one seems to be a basis of the doctrine of corporate social responsibility in its original form presented within the “gospel of wealth” movement. The second one however offers even more opportunities to discuss the responsibilities of business in today’s world. So the religious narratives cannot be ignored within business ethics. This conclusion applies, of course, to all religions, esp. the Asian ones in view of the fact of the rapid development of Chinese or Indian economies.